Political Connections, Capital Intensity, The Existence of A Risk Management Committee, and Real Earnings Management on Tax Aggressiveness - Pratiwi, Anggi; Achyani , Fatchan (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the determinants of tax aggressiveness in Indonesian consumer non-cyclical manufacturing firms listed on the Indonesia Stock Exchange between 2021 and 2024, focusing on Political Connections, Capital Intensity, Risk Management Committee, and Real Earnings Management. Using a quantitative approach, data were collected from 175 purposively selected firms with complete financial reports, consistent profitability, and statements in Indonesian Rupiah. Tax aggressiveness was measured by Effective Tax Rate, while other variables were operationalized using appropriate quantitative proxies. Multiple linear regression analysis reveals that only Capital Intensity significantly influences tax aggressiveness, whereas Political Connections, Risk Management Committee, and Real Earnings Management show no significant effect. The adjusted R² of 0.042 indicates that most variation in tax aggressiveness is explained by factors outside the scope of this study. Future research should consider larger samples, longer periods, and additional governance and earnings management variables to gain a more comprehensive understanding.